If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -63 = 2x + -7 Reorder the terms: -63 + 4x = 2x + -7 Reorder the terms: -63 + 4x = -7 + 2x Solving -63 + 4x = -7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -63 + 4x + -2x = -7 + 2x + -2x Combine like terms: 4x + -2x = 2x -63 + 2x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 -63 + 2x = -7 + 0 -63 + 2x = -7 Add '63' to each side of the equation. -63 + 63 + 2x = -7 + 63 Combine like terms: -63 + 63 = 0 0 + 2x = -7 + 63 2x = -7 + 63 Combine like terms: -7 + 63 = 56 2x = 56 Divide each side by '2'. x = 28 Simplifying x = 28
| 2p*2-6=-11 | | 97-5*x-2x=48 | | 25+100x=625 | | x-0.29x=438.07 | | 5/2•38.2 | | 10x^2+9=16x^2+9 | | m/sqrt3-11=4 | | 5x+5+4x+2=52 | | (s-6)+(8s+4)= | | -120/(-20)= | | 10+0.10a=0.35a | | 97-5*x=48+2*x | | 12(p-2.33)=8 | | x^2+15+40=4 | | 10+0.10a=0.35 | | 22-s/7=-5 | | 8×5.5/11 | | -60-7n=4+9n | | 1.5x+20= | | 0.5x^2=8x-0.625 | | 3(x-4)-5x=-2x+10 | | y=3(10-2) | | X-0.20x=485.20 | | y=3(8-2) | | 12/(-2)= | | .29x=125-x | | y=3(2-2) | | n-2.2=3.1 | | 52-(2x+6)=2(x+8)+x | | -7-3v=2v+45 | | X+.20x=485.20 | | 2n=10.6 |